Cytotoxic effects of extracts obtained from plants of the Oleaceae family: bio-guided isolation and molecular docking of new secoiridoids from Jasminum humile - Khaled Ahmed Mansour; Ahmed Elbermawi; Ahmed A. Al-Karmalawy; Mohamed-Farid Lahloub; Mona El-Neketi (Taylor & Francis Group, 2022)
Context Traditionally, Oleaceae plants are used to treat many diseases, such as rheumatism, hypercholesterolaemia, or ulcers.Objectives To investigate the cytotoxic potential of Jasminum humile L., Jasminum grandiflorum L., and Olea europaea L. (Oleaceae) extracts against selected human cancer cells lines, followed by a phytochemical investigation of the most potent one.Materials and methods The 95% ethanol extracts of aerial parts of three oleaceous plants were examined for their cytotoxicity against HepG-2, MCF-7, and THP-1 cell lines using MTT assay and doxorubicin (positive control). J. humile was bio-selected and submitted to bio-guided fractionation. Chromatographic workup of ethyl acetate and n-butanol fractions afforded two new compounds; 1-methoxyjasmigenin (1) and 1-methyl-9-aldojasmigenin (2), along with five known ones (3-7). Structures were unambiguously elucidated using 1D/2D NMR and ESI-HRMS. Isolated compounds were assessed for their anti-proliferative potential, and both selectivity index and statistical significance were determined. Molecular docking was conducted against the Mcl-1 receptor using (AZD5991) as a standard.Results Jasmoside (5) was the most potent anticancer compound showing IC50 values of 66.47, 41.32, and 27.59 µg/mL against HepG-2, MCF-7, and THP-1 cell lines, respectively. Moreover, isojasminin (4) exhibited IC50 values of 33.49, 43.12, and 51.07 µg/mL against the same cell lines, respectively. Interestingly, 5 exhibited the highest selectivity index towards MCF-7 and THP-1, even greater than doxorubicin. Molecular docking results were in full agreement with the MTT assay and the proposed SAR.Conclusion In this study, two new compounds were purified. The biological activity highlighted jasmoside (5) as a lead anticancer drug for further future investigation.